Decrease in eccentric hamstring strength in runners in the Tirol Speed Marathon. Issue 10 (6th July 2006) - Koller, A; Sumann, G; Schobersberger, W; Hoertnagl, H; Haid, C
Abstract : Background: The local muscular endurance of knee flexors, during eccentric work in particular, is important in preventing or delaying kinematic changes associated with fatigue during treadmill running. This result, however, may not be transferable to overground running. Objective: To test the hypothesis that overground running is associated with eccentric hamstring fatigue. Methods: Thirteen runners (12 male and one female) performed an isokinetic muscle test three to four days before and 18 hours after a marathon. Both legs were tested. The testing protocol consisted of concentric and eccentric quadriceps and hamstring contractions. Results: There were no significant differences between peak torque before and after the race, except that eccentric peak hamstring torque (both thighs) was reduced. Conclusion: Overground running (running a marathon) is associated with eccentric hamstring fatigue. Eccentric hamstring fatigue may be a potential risk factor for knee and soft tissue injuries during running. Eccentric hamstring training should therefore be introduced as an integral part of the training programme of runners.